Ferroptosis as a New Mechanism in Parkinson’s Disease Therapy Using Traditional Chinese Medicine - Wu, Lijuan; Liu, Meijun; Liang, Jingtao; Li, Nannan; Yang, Dongdong; Cai, Junjie; Zhang, Yong; He, Yuan; Chen, Zhigang; Ma, Tao (Frontiers in Pharmacology, 2021)
Parkinson's disease (PD) is one of the most common neurodegenerative disease. To date, among PD medications, only levodopa shows a limited disease-modifying effect on early-onset PD, but it cannot delay the progression. In 2018, for the first time, World Health Organization(WHO) included traditional Chinese medicine(TCM) in its influential global medical compendium. Traditional Chinese medicine treatment of PD has a long history. At present TCM can help to treat and prevent PD. Iron metabolism is closely associated with PD. Ferroptosis, characterized by the accumulation of lipid peroxides, is a new form of iron-dependent cell death. Public literature indicated that ferroptosis in dopaminergic neurons is an important pathomechanism of PD. TCM ave unique roles in the treatment of PD. TCM provides new ideas for the treatment of Parkinson's disease by regulating the Ferroptosis pathway.